The Effect of a Problem-Based Learning (PBL) Model Integrated with Mind Mapping on The Learning Motivation of Grade X Students - Alfianto Firdaus Wahyudi; Akhmad Fathir; Moch Haikal (PAIDAGOGIA: Jurnal Inovasi Pendidikan dan Pembelajaran, 2025)
Low student motivation for learning in the biology curriculum remains a challenge that calls for innovative instructional approaches. One alternative is the Problem-Based Learning (PBL) model integrated with the Mind Mapping technique, which is believed to promote active engagement and improve students' understanding. This study aimed to examine the effect of a Problem-Based Learning (PBL) model integrated with Mind Mapping on students' learning motivation regarding water pollution among Grade X students at MA Miftahul Ulum Bettet Pamekasan. The study employed a quantitative, quasi-experimental design with a post-test-only control group. The sample consisted of two classes: an experimental class that implemented PBL integrated with Mind Mapping and a control class that used the lecture method, each with 25 students. The research instrument was a learning motivation questionnaire. Data were analyzed using tests of normality and homogeneity, and an independent-samples t-test in Jamovi version 2.3.26. The results indicated a p-value of 0.705 (p > 0.05), indicating no statistically significant difference in learning motivation between the experimental and control groups. Therefore, it can be concluded that implementing Problem-Based Learning integrated with Mind Mapping did not have a significant effect on students' learning motivation. Nevertheless, this model is still recommended as an innovative instructional strategy that may enrich students' learning experiences.